LAW ENFORCEMENT AGAINST FOREIGN NATIONALS WHO EXCEED THE PERIOD OF STAY PERMIT IN INDONESIA - Hermawan, Ade; Sukindar; Khairunnisah (Awang Long Law Review, 2025)
Immigration problems are issues that cannot be ignored. The arrival of foreign nationals to Indonesia has an important role in supporting national development, as it can provide various benefits and advantages for the country. The mobility of foreigners in and out of Indonesia contributes to the increase of foreign exchange, especially in increasing regional income to support development and increase the amount of foreign currency deposits. This research focuses on the problems that arise when foreign nationals exceed the limit of their stay in Indonesia. This research utilizes the Empirical Juridical method with a juridical analysis approach in empirical legal studies. This approach views law as an inseparable part of human life. Law is not only considered as something abstract, but also understood through individual behavior and social dynamics in society. The study of social behavior in this context is directed at verifying the validity of the applicable law based on the empirical data obtained. Based on the research results, administrative action in immigration is closely related to selective policy as stipulated in the explanation section of Law No. 6/2011 on Immigration. Although legal provisions have regulated this, there are still cases of foreign nationals misusing their residence permits. One example of a case currently being handled by the Office of IMMIGRATION CLASS I TPI SAMARINDA shows that violations of residence permits are not criminally prosecuted, but are only subject to administrative sanctions in the form of deportation, as stipulated in Article 75 paragraph (2) letter f of Law Number 6 of 2011 concerning Immigration.